The pharmacodynamics of low and standard doses of ticagrelor in patients with end stage renal disease on hemodialysis. (1st July 2017) - Kim, Jin Sug; Woo, Jong Shin; Kim, Jin Bae; Kim, Woo-Shik; Lee, Tae Won; Kim, Kwon Sam; Ihm, Chun Gyoo; Kim, Weon; Jeong, Kyung Hwan
Abstract: Background: Patients with end-stage renal disease (ESRD) on maintenance hemodialysis (HD) respond poorly to clopidogrel. We assessed the utility of low-dose ticagrelor in ESRD patients on maintenance HD. Methods: In this single-center, prospective, randomized pharmacodynamic study, 52 ESRD patients on HD were prescribed clopidogrel (300 mg loading dose [LD], then 75 mg daily), standard-dose ticagrelor (180 mg LD, then 90 mg twice daily), or low-dose ticagrelor (90 mg LD, then 90 mg daily) for 14 days. Platelet function was evaluated before and after therapy via light transmittance aggregometry and the VerifyNow™ P2Y12 assay. Results: The adenosine diphosphate (ADP)-induced maximal extent of platelet aggregation differed significantly between the low-dose ticagrelor and clopidogrel groups (ANCOVA, p  = 0.04 after stimulation with 5 μmol/L ADP; p  < 0.01 after stimulation with 20 μmol/L ADP). Inhibition of platelet aggregation increased significantly in the order of clopidogrel, low-dose ticagrelor, and standard-dose ticagrelor, as revealed by adjusted intergroup comparison analysis (ANCOVA, p  = 0.04 after stimulation with 5 μmol/L ADP; p  = 0.005 after stimulation with 20 μmol/L ADP). The rates of onset of the antiplatelet effect curves from 0 to 5 h after administration of the LDs were greater in the standard- and low-dose ticagrelor groups than in the clopidogrel group. Significant sequential reductions in P2Y12 reaction units were noted, in the following order: clopidogrel, low-dose ticagrelor, and standard-dose ticagrelor (ANCOVA, p  < 0.001). No bleeding occurred in the low-dose ticagrelor group. Conclusions: Low-dose ticagrelor afforded greater platelet inhibition than did clopidogrel in ESRD patients on HD.